Ecuador: determinantes de la tasa de desempleo, periodo 1990 - 2020. - Vargaz Hernandez, Kelly Andrea; Zuñiga Ordoñez, Fanny Piedad (My University, 2021)
Unemployment is a macroeconomic variable of major emphasis in a country, it is considered a global problem that directly affects all economies. The present research aims to analyze the determinants that affect the variation of the unemployment rate in Ecuador period 1990-2020 through an econometric model of Ordinary Least Squares, for which the historical information of the bases was collected, processed and analyzed. of data from the World Bank and the Central Bank of Ecuador. The results obtained from the multiple linear estimation model present a coefficient of determination of 0.8155, which indicates that 81.55% of the time the unemployment rate in the country is explained by the independent variables, at the same time with the application of the tests. The White test and Shapiro-Wilks corroborated the validity of the model and the significance of the set of variables. It is concluded that as the Gross Domestic Product and remittances increase, the unemployment rate decreases, while as inflation and the population increase, the unemployment rate will also increase and vice versa. In addition, to face this problem, it is important to develop and implement economic policies aimed at reducing unemployment levels in the country.
El desempleo es una variable macroeconómica de importante énfasis de un país, se considera un problema global que afecta de manera directa a todas las economías. La presente investigación tiene como objetivo analizar los determinantes que inciden en la variación de la tasa de desempleo en el Ecuador periodo 1990-2020 mediante un modelo econométrico de Mínimos Cuadrados Ordinarios, para la cual se recopiló, procesó y analizó la información histórica de las bases de datos del Banco Mundial y del Banco Central del Ecuador. Los resultados obtenidos del modelo de estimación lineal múltiple presentan un coeficiente de determinación de 0.8155 lo que indica que el 81.55% de las veces a la tasa de desempleo en el país es explicada por las variables independientes, a la vez con la aplicación de las pruebas de White test y Shapiro-Wilks se corroboró la validez del modelo y la significancia del conjunto de variables. Se concluye que a medida que el Producto Interno Bruto y las remesas se incrementen la tasa de desempleo se reduce, mientras que a medida que la inflación y la población aumenten la tasa de desempleo también se incrementará y viceversa. Además, para hacer frente a esta problemática es importante la elaboración e implementación de políticas económicas tendentes a reducir los niveles de desempleo en el país.
Keywords: DESEMPLEO; MODELO DE ESTIMACIÓN LINEAL; CRECIMIENTO ECONÓMICO; INFLACIÓN